2010
DOI: 10.1177/1468798410372159
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s exploration of semiotic resources during unofficial computer activities in the classroom

Abstract: The article describes and discusses the learning potential of unofficial techno-literacy activities in the classroom with regards to Swedish 7—8-year-olds’ exploration of semiotic resources when interacting with computers. In classroom contexts where every child works with his or her own computer, such activities tend to take up a substantial amount of time. The children have access to a wide range of sites and programs and show an interest in discovering these resources. The article thus explores a previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 17 publications
3
26
0
6
Order By: Relevance
“…Elmfeldt & Erixon (2007), and Erixon et al (2012) relate to North American media philosophy and theories on media ecology together with educational sociology (Basil Bernstein). Other theoret-ical standing points are social semiotic and ethnography (Björkvall & Engblom, 2010), Systemic Functional Linguistics , genre theory and multimodality (Hultin & Westman, 2013 a,b;Lundström & Olin-Scheller, 2010), the latter in combination with narrative theory and visual literacy .…”
Section: Findings In the Included Swedish Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elmfeldt & Erixon (2007), and Erixon et al (2012) relate to North American media philosophy and theories on media ecology together with educational sociology (Basil Bernstein). Other theoret-ical standing points are social semiotic and ethnography (Björkvall & Engblom, 2010), Systemic Functional Linguistics , genre theory and multimodality (Hultin & Westman, 2013 a,b;Lundström & Olin-Scheller, 2010), the latter in combination with narrative theory and visual literacy .…”
Section: Findings In the Included Swedish Studiesmentioning
confidence: 99%
“…Seven studies deal with secondary and upper secondary school (Elmfeldt & Erixon, 2007;Erixon et al, 2012Lundström & Olin-Scheller, 2010) and five deal with preschool and primary school Björkvall & Engblom, 2010;Hultin & Westman, 2013a;2013b;Sofkova Hashemi, 2013). Swedish as a school subject has a firmer identity in secondary and upper secondary studies than in preschool and primary school.…”
Section: Findings In the Included Swedish Studiesmentioning
confidence: 99%
“…Studies on multiliteracies and classroom context are very important. Björkvall & Engblom (2010) have shown that unofficial computer activities (their term) guided by the interests of the child have learning potential, for example in offering 2. For an overview of reading and writing pedagogies in relation to new literacies, see Andersson (2011).…”
Section: Theoretical Background: Digital Literacies New Literacies Amentioning
confidence: 99%
“…By focusing on everyday use, the researcher is seeking to understand how the material resources are 'semiotized' i.e. transformed into semiotic resources (Bjorkvall & Engblom, 2010). In the case of digital art-making, a focus on everyday use might take the form of gathering 'talk around text' (Lillis, 2008, p. 355) to see how various social influences are unfolding through semiotic processes that lead to the young child's artwork.…”
Section: Methodsmentioning
confidence: 99%